Psychometric properties of a Food Buying Styles Scale (EEC-ALI) in University Students - Denegri, Marianela; García, Constanza; González, Nicolle; Elgueta, Herman; Hueche, Clementina; Schnettler, Berta (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The object of the present reserach was to assess the psychometric properties of the Food Buying Styles Scale (Escala de Estilos de Compra de Alimentos – EEC-ALI) based on the Buying Styles Scale adapted by Denegri, Peñaloza, Elgueta and Sepúlveda (unpublished manuscript). This scale assesses planning, impulsiveness and compulsiveness with regards to food buying behavior. The sample consisted of 369 university students, male and female, from northern, central and southern Chile. We examined reliability and validity indicators. The analyses showed that the scale has appropriate psychometric properties, suggesting that the instrument is adequate for its use in the analysis of food buying styles in young people and specifically university students.